Pengaruh Pengungkapan Corporate Social Responsibility, Profitabilitas, Leverage, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Valentino, Ardivan Dicha; Setiawan, Putu Ery (Fakultas Ekonomi Universitas Samudra, 2024)
The aim of this research is to obtain empirical evidence on how corporate social responsibility (CSR) disclosure, profitability, leverage, and firm size influence firm value. Firm value is an indicator that shows company performance through stock price movements. This study was conducted on SRI-KEHATI indexed companies during the 2020-2022 period. The data collection method uses non-participant observation. The sampling method uses non-probability sampling with purposive technique. The collected data was analyzed using multiple linear regression. The research results show that CSR disclosure has no influence on firm value, profitability and leverage have a positive influence on firm value, and firm size has a negative influence on firm value